Advances in Sustainable Finance in Energy Sectors - Beata Zofia Filipiak (Energies)
Climate initiatives are not only intensified by politicians and international organizations, but climate policy is also subject to changes resulting from various factors, the sources of which can be seen in socio-economic problems, incorrect investment decisions and the consequences of ESG risk [...]